Fungsi Dinas Penanaman Modal Dan Pelayanan Satu Pintu Dalam Penerbitan Surat Izin Praktik Bagi Bidan Di Kota Jambi - Dwinarta, Gilang; Budhiartie, Arrie; Zulkarnain, Iskandar (Lex Librum : Jurnal Ilmu Hukum, 2025)
The Investment Coordinating Board and One-Stop Integrated Services are responsible for issuing permits, including Midwife Practice Permits (SIPB), which are mandatory for health workers, particularly those practicing independently, to provide health and midwifery services. Following the implementation of Health Law Number 17 of 2023 alongside the Job Creation Law, modifications have been noted in the process for applying for and obtaining the Midwife Practice License (SIPB). This research aims to analyze (1) the jurisdiction of the Investment and One-Stop Integrated Service Office in granting midwife practice permits in accordance with current laws and regulations, and (2) the procedure for issuing midwife practice permits in Jambi City following the implementation of Health Law No. 17 of 2023. This normative legal study involves analyzing legal resources using a statutory and conceptual approach, interpreted descriptively and deductively to formulate findings that answer the specified legal concerns in the form of statements. The research findings indicate that (1) the authority of the Investment and One-Stop Integrated Services Office to issue midwife practice permits is derived from the Jambi City Government, considering the stipulations in the regulations governing risk-based business licensing in the health sector. The process for issuing midwife practice permits commences with the administrative completeness phase, followed by a site review conducted by the health department and the Investment and One-Stop Integrated Services Office, then proceeds to registration, issuance of feasibility approval, and culminates in the issuance of the practice permit by the Jambi City Government. It is advisable that a regional regulation be swiftly enacted in the future to serve as an implementing regulation for the issuance mechanism of health practice permits, thereby enhancing the efficiency and effectiveness of permits in safeguarding the community and contributing to the City of Jambi's PAD.